Digital Authentication for Wireless Domain Using Variable Marking of Multiple Secret Signatures and its Practical Implication in E-Stamp Authentication - Bose, Saikat; Gangwar , Mohit; Arjariya, Tripti (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The work emphasizing dynamic authentications for transmitted e-documents like e-stamp paper under wireless environments through variable circular concealment of multiple invisible signature images governed by the encryption of secret key and the session random number. Additionally region wise separate bit casting strategy and dynamical bit sequencing concepts for multiple signatures ensuring greater security and robustness. Additional multi-copy signature marking on all non-overlapping areas of the document cover image, along with noticeably varied bit encoding strategies on each modified pixel byte coefficient for the cover image sub blocks, essentially improve protection and signature recovery from attacks. The reverse transformed bit coded pixel byte components for the sub blocks within the spatial domain ranges are maintained while the threshold range driven bit creation notion operates admirably under attacks. Finally, since all the secret information and the random number are likewise provided to the receiver, the securely marked signature bits may then be recognized there in the appropriate relevant ordering from the corresponding forward transformed sub block pixel byte elements. Significantly improved performance of our system in contrast to earlier efforts has been proven by significant experimental results, which also highlight solid trusted authentication and confidentiality scenarios as the key security issues.